Glocalization in International Early Childhood Islamic Education - Eliyyil Akbar; Abdul Rahman Assegaf; Muqowim Muqowim; Irfan Tamwifi; Zulkarnain Zulkarnain (LPPM Universitas Pahlawan Tuanku Tambusai, 2023)
The diversity of tribes and nations is a necessity of creation, because God Almighty sent his people to learn to live in harmony. The diversity of world culture is shown through the educational process so that it is able to meet the needs of students who do not eliminate local cultural values which is called glocalization. The importance of glocalization is to observe the rise of internal and external intolerance in the name of religion on a local and global scale which has caused divisions from various parties. This research is to find out the criteria and objectives of glocalization of international early childhood Islamic education. This paper aims to explain glocalization in the world of International Early Childhood Islamic Education. This study uses a qualitative phenomenological approach. Data collection techniques using observation, interviews, and documentation. Determination of the source sample by purposive sampling with certain criteria that meet the data needs. Data analysis uses the Miles and Huberman model with data collection, data reduction, data presentation as well as conclusion and verification. These findings indicate that the criteria for glocalization of international Islamic education at the Islamic International School PSM Magetan Indonesia are bi'ah Islamiyah, the language of instruction is English, using international branding. The goal of glocalization of international standard PAUD at the Islamic International School PSM Magetan is to improve spiritual, emotional, intellectual, foster an international spirit without eliminating the spirit of nationalism.